VENTURE BUSINESS AS A PROGRESSIVE FORM OF SPREADING INNOVATION - Soliar, Viktoriia (SWorld-Ger Conference proceedings, 2025)
The requirement to bring new products and technologies to a large market to ensure the payback of the costs of their creation and to obtain high profits necessitates the cooperation of corporations and venture business. Today, cooperation of large corpora